2018
DOI: 10.3329/bhj.v33i2.39305
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Inflammatory Marker and Glycemic Control in Patients with Ischemic Heart Disease

Abstract: Background: Recent evidence suggests that inflammatory markers and poor glycemic control are significantly associated with the development of cardiovascular complications. The purpose of this study was to determine the association between inflammatory marker (CRP) and glycemic status (HbA1c) in ischemic heart disease patients. Method: This cross sectional study was performed on 668 patients of ischemic heart disease in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, who underwent Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The mean age was found (53.0%±13) years with a range from 19-84 years, significantly higher than the control group. In a similar report, Muhammad et al 12 found that the mean age of the study population was 51.5±9.5 years.The majority (65.6%) of the patients were female (65.7%) in the present study which is in concordance with Muhammad et al 11 The present study suggests that the association between CRP and diabetes risk was stronger in women than in men, which is similar to the Huet al 13 and Pichandi, et al 14 and discordance to Ahemed et al 15 Gender differences in plasma CRP are well documented, with circulating levels being higher in women. [16][17][18] This difference is not fully understood but could be related to gender differences in both visceral and subcutaneous fat, an important factor in CRP levels 18 or to differences in estrogen, which is known to increase CRP level.…”
Section: Discussionsupporting
confidence: 91%
“…The mean age was found (53.0%±13) years with a range from 19-84 years, significantly higher than the control group. In a similar report, Muhammad et al 12 found that the mean age of the study population was 51.5±9.5 years.The majority (65.6%) of the patients were female (65.7%) in the present study which is in concordance with Muhammad et al 11 The present study suggests that the association between CRP and diabetes risk was stronger in women than in men, which is similar to the Huet al 13 and Pichandi, et al 14 and discordance to Ahemed et al 15 Gender differences in plasma CRP are well documented, with circulating levels being higher in women. [16][17][18] This difference is not fully understood but could be related to gender differences in both visceral and subcutaneous fat, an important factor in CRP levels 18 or to differences in estrogen, which is known to increase CRP level.…”
Section: Discussionsupporting
confidence: 91%